PENEGAKAN HUKUM JUDI ONLINE YANG DILAKUKAN SAT.RESKRIM POLRESTABES MEDAN BERDASARKAN PENERAPAN KUHP DAN UNDANG-UNDANG NO. 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NO. 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Iqbal Ramadhan Satria Prawira; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (USU LAW JOURNAL, 2018)
ABSTRACT It is not an easy thing to complete gambling, there needs to be a legal regulation that crack down on the perpetrators of gambling crime. Regulations on gambling are originally stipulated in Article 303 of the Criminal Code, subject to imprisonment of up to 2 (two) years 8 (eight) months or a maximum fine of Rp. 90.000, - (ninety thousand rupiah). With the issuance of Law No. 7 of 1974 on Gambling Control, Article 2 Paragraph (1) shall contain the penalty for the criminal act of gambling Article 303 paragraph (1) of the Criminal Code shall be changed to imprisonment for a maximum of 10 (ten) years or a maximum fine of Rp. 25.000.000, - (twenty five million rupiah). Then change Article 542 to Article 303 bis paragraph (1) of the Criminal Code with threatened to be 4 (four) years imprisonment or a maximum fine of Rp. 10.000.000 (ten million rupiah), then Article 303 bis verse (2) of the Criminal Code with a maximum imprisonment of 6 (six) years or a maximum fine of Rp. 15.000.000 (fifteen million rupiah). But the investigation of the crime of gambling was still facing obstacles when faced with the gambling proof process through the internet, because in the Criminal Procedure Code is not regulated the elements containing information technology, while in the case of gambling through the internet ("internet gambling") all done through the internet media. To overcome gambling conducted on the internet, has been issued Law No. 11 Year 2008 on Information and Electronic Transactions. When dealing with "internet gambling" there will still be new problems that will arise, especially regarding the evidence. If, in ordinary gambling, the tools to be used for gambling such as dice or cards and money used for betting are enough to be used as evidence. Whereas, in "internet gambling" gambling is done like a normal computer game. On gambling made via internet bets are paid not from hand to hand, but are transferred directly by writing credit card account numbers over the internet anyway.   Keywords : Law Enforcement; Internet Gambling; and Polrestabes Medan.